2017
DOI: 10.1097/qai.0000000000001290
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric HIV Disclosure Intervention Improves Knowledge and Clinical Outcomes in HIV-Infected Children in Namibia

Abstract: Objectives:Using routinely collected data, we evaluated a nationally implemented intervention to assist health care workers and caregivers with HIV disclosure to children. We assessed the impact of the intervention on child's knowledge and health outcomes.Methods:Data were abstracted from national databases and patient charts for HIV-infected children aged 7–15 years attending 4 high-volume HIV clinics in Namibia. Disclosure rates, time to disclosure, and HIV knowledge in 314 children participating in the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
3
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 32 publications
1
45
3
1
Order By: Relevance
“…Our study showed that counsellors were frequently the primary individuals involved in the disclosure process in our sites. However, in the literature describing interventions to support disclosure, there is no specific mention of counsellors having a role in this process , as usually “healthcare workers” or “providers” are cited as being involved with disclosure. Counsellors and social workers may have been combined into the designation of “provider,” and play key roles in the delivery of care.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that counsellors were frequently the primary individuals involved in the disclosure process in our sites. However, in the literature describing interventions to support disclosure, there is no specific mention of counsellors having a role in this process , as usually “healthcare workers” or “providers” are cited as being involved with disclosure. Counsellors and social workers may have been combined into the designation of “provider,” and play key roles in the delivery of care.…”
Section: Discussionmentioning
confidence: 99%
“…This will also reduce the estimated 29% of new infections from patients who are not virally suppressed. To improve pediatric adherence, Namibia plans to roll out a standardized pediatric HIV disclosure program that has been demonstrated to improve HIV outcomes, including HIV VL suppression [38], and to expand teen clubs and other community-based HIV care and treatment programs for adolescents [24, 37]. …”
Section: Discussionmentioning
confidence: 99%
“…7,12,17 Disclosure of serostatus is also positively associated with engaging in fewer acts of unprotected anal and vaginal sex, facilitating partner HIV testing, and improving ART adherence by reducing the need to hide medications from partners. 18,19 The link between disclosure and adherence to ART is vital, as adherence is critical to maximizing the clinical benefits of ART and is the most reliable determinant of patient survival.…”
Section: Benefits Of Hiv Serostatus Disclosurementioning
confidence: 99%
“…9 In addition to preventing disease transmission, evidence suggests that disclosure can positively impact physical and psychological health by improving ART adherence, clinical care retention, and social relationships, as one no longer has to hide medications or doctor's appointments. 12,15,16 Adolescents living with HIV have an ethical right to know their serostatus. Given the health and social benefits and ethical value of disclosing HIV serostatus-and the potential negative implications of not disclosing-this article outlines and provides justification for bridging the current gap between adolescent and adult HIV serostatus disclosure policies in the United States.…”
mentioning
confidence: 99%